Effect of Prescription Drug Coupons on Statin Utilization and Expenditures: A Retrospective Cohort Study. Issue 1 (28th August 2016) - Daubresse, Matthew; Andersen, Martin; Riggs, Kevin R.; Alexander, G. Caleb
Abstract : Importance: Drug coupons are widely used, but their effects are not well understood. Objective: To quantify the effect of coupons on statin use and expenditures. Design: Retrospective cohort analysis of IMS Health LRx LifeLink database. Setting: U.S. retail pharmacy transactions. Participants: Incident statin users who initiated branded atorvastatin or rosuvastatin between June 2006 and February 2013. Main Outcomes and Measures: Monthly statin utilization (pill‐days of therapy), switching (filling a different statin), termination (failure to refill statin for 6 mo), and out‐of‐pocket and total costs. Results: Of 1.1 million incident atorvastatin and rosuvastatin users, 2% used a coupon for at least one statin fill. At 1 year, compared with noncoupon users, those who used a statin coupon on their first fill were dispensed an equal number of monthly pill‐days (23.7 vs 23.8), were less likely to switch statins (14.4% vs 16.3%), and were less likely to have terminated statin therapy (31.3% vs 39.2%). At 4 years, coupon users were more likely to have switched (45.5% vs 40.8%) and less likely to have terminated statin therapy (50.6% vs 61.1%) compared with noncoupon users. Those who used greater numbers of coupons were substantially less likely to switch and terminate statin therapies. Monthly out‐of‐pocket costs were lower among coupon than noncoupon users at 1 year (9.7 vs 15.1), but total monthly costs were qualitatively similar (115.5 vs 116.9). At 4 years, monthly out‐of‐pocket costs among coupon users remained lower (14.3 vs 16.6) compared with noncoupon users. Sensitivity analyses supported the main results. Conclusions: Coupons for branded statins are associated with higher utilization and lower rates of discontinuation and short‐term switching to other statin products.